SEBUAH PURA BAGIAN DARI PERJALANAN DANGHYANG NIRARTA - Komang Trisna Dewi (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2021)
Sad Kahyangan Jagat is one of six temples. It stands majestically atthe southwestern tip of Bali on a steep, high rock platform and protrudesinto the sea. This temple is located in the village of Pecatu, South KutaDistrict, Badung Regency and this temple is easily accessible. UluwatuTemple is divided into three parts; Utama Mandala, Madya Mandala, andNista Mandala. At Utama Mandala there are prasada and pelinggih in theform of Meru Tumpang Tiga. In Madya Mandala there are no pelinggih.Whereas in the southern Mandala Nista called Dalem Be Pvt, there areamong others prasada, where the mokshanya Danghyang Dwijendra isside by side with a monument in the form of two boats used to sail whencoming to Bali. Uluwatu Temple is a well-known tourist attraction in allforeign countries, although it is already a place that is very popular withtourists does not necessarily make people forget some things that must bedone by visitors (tourists) when it comes to temples. The visitors must usecloth (relapsed) and scarves so that when entering the temple area,harmony, sacred values can be interpreted by visitors. Regulations relatingto the ethics of visitors who come to Uluwatu Temple must adhere to theapplicable rules made by Bendesa Adat.